STUDENTS’ MORAL PROBLEM BASED ON TEACHER’S PERSPECTIVE: IMAM AL GHAZALI’S CONCEPT - Yulianto, Wahyu Dwi; Mubarokah, Laelah Al (PEOPLE: International Journal of Social Sciences, 2020)
This paper aims to analyze the moral problems that occur in the world of education through Imam Al Ghazali’s concept. He is a Muslim philosopher and theologian. Likewise, he has a book entitled Ihya ‘Ulumuddin in which discuss about moral education. The subject is one of the students in TPA (After school Qur’an program) at Baiturrahim Sleman Yogyakarta, Indonesia. The background of this study is a lot of Indonesian students have a lack of attitude and moral toward their teacher. This study uses qualitative methods with interviews. The findings revealed several factors that led to the crisis of moral education in students, such as those that lowered religious education material. The conclusion is to know the background of the moral education problem and using Imam Al Ghazali’s concept as a role model to minimize the occurrence of moral crisis among Indonesian students.